Identity, Ethics, and Ethos in the New Testament - Malan, François Stephanus; Watt, Jan Gabriël van der (Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche, 2006)
Biographical note: Jan van der Watt, University of Pretoria, South Africa.